Prevalence of carotid artery calcification detected by digital panoramic radiographs in a sample of Yemeni dental patients - Helmi, Jameel; Alhariri, Zakria; Al-Jawfi, Khaled; Shamala, Anas (Universidad de Concepci?n, 2019)
Background: Carotid artery calcification (CAC) is one of risk factors of cardiovascular disorders (CVDs). Digital panoramic radiographs can detect it. Aim of the study: This study aimed to determine the prevalence of CAC detected by digital panoramic radiographs in a sample of Yemeni dental patients. Materials and Methods: An observational and analytical cross-sectional study was used to investigate a convenience sample of 443 patients. These patients were interviewed face-to-face for their socio-demographic information and their medical background regarding CVDs and associated risk factors. The researchers for detection of CAC assessed the digital panoramic radiographs. Results: High income and middle-aged patients were risk factors of CVDs significantly associated with increased incidence of CAC (42 patients (9.5%) and 32 patients (7.2%), respectively). Patients with a previous medical consultation, previous medications and family history of CVDs revealed a significant higher prevalence of CAC (p=0.001). Conclusion: There was an increased prevalence of CAC detected on digital panoramic radiographs, as a risk factor of CVDs. CAC was more common in females than males.